Sharing the burden? Empirical evidence on corporate tax incidence - Nadja Dwenger; Pia Rattenhuber; Viktor Steiner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This study empirically investigates the direct incidence of the corporate income tax through wage bargaining, using an industry-region level panel data set on all corporations in Germany over the period 1998 to 2006. Our measure of direct incidence for the first time accounts for employment effects which result from tax induced wage changes. Workers share in reductions of the CIT burden; yet, direct incidence is small and confined to 0.19 0.29. Thus, the net effect of wage bargaining on the corporate wage bill, after an exogenous 1 decrease in the CIT burden, is as little as 19 to 29 cents. This is about half of the effect obtained in prior literature under the assumption that employment remained constant. A focus on wages alone leads to an overestimation of direct tax incidence.
Keywords: H22; H25; J21; 330